The Influence of Parent Brands Commitment On Consumers' Atitude Toward Co-Branding Between Those Brands - Azzah Nur Aisyah, Reza Ashari Nasution (ITB, 2010)
This paper examines the influence of parentbrands' commitment on consummers' attitude toward cobranding. Co-branding refers to the combination of two brand names to lauch a single and unique product for a short to long term cooperation. Two experiments were conducted to test the hypotheses. The 82 subjects were exposed to two sessions of experment; evaluations on each brand with no cobranding. evaluations on co-branding. Consumers' attitude was derived through obtaining consumers' perception on brand personality and favorability. The findings showed that parent brands wtih high commitment received more positive attitude compared to parent brands with low commitment